2017
DOI: 10.11646/zootaxa.4362.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Species of Macrostomum (Macrostomorpha: Macrostomidae) from the coastal region of Lima, Peru, with comments on M. rostratum Papi, 1951

Abstract: Species of Macrostomum are present in almost all regions of the world. These flatworms occur in different kinds of environments, from freshwater to marine ecosystems. Although Peru is considered one of the megadiverse countries in South America, little is known about freshwater microturbellarians in this country. Here we report the presence of M. rostratum Papi, 1951 for the first time in Peru, in a coastal brackish water wetland, and that of M. quiritium Beklemischev, 1951 and M. tuba Graff, 1882 in an inland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 933 publications
(8 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…Identification. The morphology and genital system agree with previous observations by Adami et al (2017) and Reyes et al (2017). Living mature individuals about 1,600 µm long, with maximum width of 400 µm (Fig.…”
Section: Stenostomumsupporting
confidence: 91%
See 3 more Smart Citations
“…Identification. The morphology and genital system agree with previous observations by Adami et al (2017) and Reyes et al (2017). Living mature individuals about 1,600 µm long, with maximum width of 400 µm (Fig.…”
Section: Stenostomumsupporting
confidence: 91%
“…Macrostomum quiritium have been cited for Russia, Poland, and Switzerland (Schärer et al 2011) and was recently reported in the Neotropical region (Adami et al 2017). In contrast to the specimens described here, the Peruvian M. quiritium reported by Reyes et al (2017) are slender.…”
Section: Stenostomumcontrasting
confidence: 39%
See 2 more Smart Citations
“…recognition of M. hanatum, still listing M. giganteum as synonymous to M. lineare). Taken together, it is unsurprising that while there has been some recent studies of species diversity within Macrostomorpha in general (e.g., Schockaert 2014;Sun et al 2014;Janssen et al 2015;Fang et al 2016;Reyes & Brusa 2017;Lin et al 2017a, b;), taxonomic research within Microstomidae from even the last 50 years has been restricted to a very few articles (Faubel 1974(Faubel , 1984Rogozin 2015;Atherton & Jondelius 2018 a,b).…”
Section: Introduction and Aimsmentioning
confidence: 99%